Duplication and Functional Divergence of Branched-Chain Amino Acid Biosynthesis Genes in Aspergillus nidulans - Joel T. Steyer (American Society for Microbiology, 2021)
Branched-chain amino acid (BCAA) biosynthesis is important for pathogenic fungi to successfully cause disease in human and plant hosts. The enzymes for their production are absent from humans and, therefore, provide potential antifungal targets.